Amyloid cast nephropathy: A rare presentation of multiple myeloma–associated light chain amyloidosis. Issue 1 (June 2022) - Reis, Marina; Rodrigues, Ana; Cristovão Maques, Joana; Góis, Mário; Sousa, Helena; Nolasco, Fernando
Introduction: Monoclonal immunoglobulins can cause a variety of histologic patterns of kidney injury, depending on the physicochemical properties. Multiple myeloma manifests more often as light-chain nephropathy. On the other hand, light-chain amyloidosis leads to glomerular and vascular amyloid deposits, but a less common presentation with amyloid casts has also been described. Rarely, more than one histologic pattern can be present in the same patient. Case report: We report a case of a 73-year-old man, diagnosed with multiple myeloma that 8 months after achieving partial response to chemotherapy develops acute kidney injury and nephrotic syndrome. Kidney biopsy revealed features of light-chain nephropathy, amyloid cast nephropathy, and glomerular and vascular amyloid deposits. Immunofluorescence was positive for IgA (++) and lambda chains (+++) and negative for kappa chains. After the diagnosis of multiple myeloma-associated light-chain amyloidosis, chemotherapy was initiated; unfortunately, the patient died 1 month after the diagnosis. Conclusion: Amyloid casts, isolated or accompanied by other renal or extra-renal amyloid deposits, are another form of tubular toxicity caused by dysproteinemias and should be systematically screened in kidney biopsies.